Implementasi Metode Pervasive Menggunakan Protokol UDP Pada Raspberry Pi dan myRIO - Joniar Dimas Wicaksono; Wijaya Kurniawan; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Smart home environment is an environment in which there are equipment that can communicate with each other and can be monitored or controlled remotely through the internet. With this, it will make it easier for humans to control equipment at home. For now the use of home appliances that can be a smart home still requires difficult configuration. Pervasive is a method that faciliting humans without configure device. The system of this pervasive method by broadcast information itself and storing information other devices. To improve the performance and efficiency of this system, the protocol will be used is UDP protocol. Where this protocol is a lightweight protocol and does not require large memory. The system implemented on Raspberry Pi 3 as host and NI myRIO as client. This device is programmed by LabVIEW by deploying programs. Program will be made according to the system flow that is with the state machine where on each device can do discovery for the devices know each other. From the results of testing in this study, for discovery device on the host is 56,417ms, while the discovery on the client is 251.067ms. So the whole discovery process is 313,417ms. Whereas if the host fails, the time it takes the client to reconnect is 10384,23ms. For sending data between host and client, for data transmission sensor takes 58.263ms, LED control takes 5350,926ms, and for push button takes 255,696ms.